A 38.4 nW, 1.2 V, 250-Hz, 2nd-Order gm – C LPF With Degenerative SCP Transconductors Achieving 800-mVPP Input Range and 82.1- μVrms IRN for ECG Acquisition - Surachoke Thanapitak; Prajuab Pawarangkoon; Wanlop Surakampontorn; Rafidah Ahmad; Ruhaifi Abdullah Zawawi; Asrulnizam Abd Manaf; Suriya Adirek; Chaiyan Chanapromma (IEEE Transactions on Circuits & Systems II Express Briefs, 2024)
In this brief, a $2{^{\text {nd}}}$ -order $g_{\mathrm { m}} - C$ lowpass filter with a practical input linear range of $400~{\mathrm { mV}}_{\mathrm { P}}$ dedicated to ECG signal acquisition is proposed. This filter employs a degenerative source-coupled-pair circuit as a $g_{\mathrm { m}}$ cell. It enhances the linear input range by a factor of $\times 4$ compared with the source follower filter. Additionally, to mitigate the effect of current source mismatch, a dynamic element matching technique is applied. By doing so, HD2 is suppressed more than 1.5 dB over the entire passband frequency. This proposed filter is implemented in a $0.18~\mu $ m CMOS process. It offers a 250-Hz bandwidth with input-referred noise and a dynamic range of $82.1~\mu {\mathrm { V}}_{\mathrm {\mathrm {rms}}}$ and 67.34 dB, respectively. The power consumption of 38.4 nW is achieved with a 1.2 V supply. Compared with other recent nano-power filters, the proposed filter provides the highest linear input range with competitive Figure-of-Merit to the top-tier designs. It is therefore beneficial to the practical implementation of a low-power ECG acquisition system.
Keywords: Analog and Mixed-Signal Circuit Design; Acoustic Wave Resonator Technologies; Semiconductor materials and devices